2015
DOI: 10.1111/ajt.13058
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Profiles of Unexpected DCDD Donors Do Not Indicate a Role for Exogenous Fibrinolysis

Abstract: It has been suggested that vascular stasis during cardiocirculatory arrest leads to the formation of microvascular thrombi and the viability of organs arising from donation after circulatory determination of death (DCDD) donors may be improved through the application of fibrinolytic therapy. Our aim was to comprehensively study the coagulation profiles of Maastricht category II DCDD donors in order to determine the presence of coagulation abnormalities that could benefit from fibrinolytic therapy. Whole blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
1
14
1
Order By: Relevance
“…Moreover, several studies have indicated that hypoxia due to circulatory arrest (as occurs in a dying person) is associated with a pronounced stimulation of the fibrinolytic system because of the release of endogenous plasminogen activators. 2,3 In accordance with this, Vendrell et al 4 recently reported evidence of clinically relevant endogenous hyperfibrinolysis in DCD donors (Maastricht type II). These investigators, therefore, argued against the need for additional fibrinolytic therapy in DCD donors.…”
supporting
confidence: 56%
“…Moreover, several studies have indicated that hypoxia due to circulatory arrest (as occurs in a dying person) is associated with a pronounced stimulation of the fibrinolytic system because of the release of endogenous plasminogen activators. 2,3 In accordance with this, Vendrell et al 4 recently reported evidence of clinically relevant endogenous hyperfibrinolysis in DCD donors (Maastricht type II). These investigators, therefore, argued against the need for additional fibrinolytic therapy in DCD donors.…”
supporting
confidence: 56%
“…Several years ago, Porte and Clavien highlighted the fact that platelet activation is reduced and coagulation altered early after death, with less stable clot formation and marked activation of the fibrinolytic system . More recently, our group used ROTEM to show that potential uDCD donors universally suffer hyperfibrinolysis at the moment death is declared . Other groups have used thromboelastometry to study patients suffering CA, and it appears that the incidence of hyperfibrinolysis increases in relation to the length of arrest and warm ischemia .…”
Section: Discussionmentioning
confidence: 99%
“…(22) More recently, our group used ROTEM to show that potential uDCD donors universally suffer hyperfibrinolysis at the moment death is declared. (23) Other groups have used thromboelastometry to study patients suffering CA, and it appears that the incidence of hyperfibrinolysis increases in relation to the length of arrest and warm ischemia. (24) When organs and tissues suffer progressive ischemia, thrombomodulin, an integral membrane protein expressed on the surface of endothelial cells, is induced.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation studies performed in DCD donors help explain why a microvascular clot does not form even in the presence of a cardiac standstill. Using rotational thromboelastometry, our group has shown that potential uDCD donors universally suffer hyperfibrinolysis at the moment death is declared, obviating the need for fibrinolytic therapy . Other groups have used thromboelastometry to study patients suffering cardiac arrest, and it appears that the incidence of hyperfibrinolysis increases in relation to the length of arrest and warm ischemia time (WIT) .…”
Section: Pathogenesis Of Ischemic‐type Biliary Lesionmentioning
confidence: 99%